Economics of Maize (Zea mays L.) production in Nigeria and Maize traditional utilization - Adiaha, Monday Sunday (International Journal of Scientific World, 2017)
A survey on economics of Maize (Zea mays L.) production in Nigeria and its traditional utilization was conducted. Result of the survey presented maize having the potential of increasing the economy of the nation. Analyzed data presented maize been able to increase the income of the local people and foreign exchange earnings, as observed where price of the crop during 1980 (2500) stands below price at 1989 (14000). Increased in land utilization with increase in years was observed in data analyzed as 1980 (95600 hectares) of land area stands below (211740) in1989. Traditional utilization of maize has been found to include where the crop is been used as herbal medicine, as food, in traditional religion, in-addition to where the crop is been utilized in marital rituals.